Analisis gaya bahasa sarkasme terhadap pejabat pada saat memberikan bantuan pada bencana alam Sumatera 2025 - Suci septia Suci septia anggraini (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The flash floods and landslides that struck Sumatra in November–December 2025 not only left deep sorrow for nearly 1,000 affected families, but also triggered a wave of sharp criticism regarding the government’s communication during emergency situations. Much of this criticism was expressed in the form of harsh, sarcastic remarks that highlighted the insensitivity and slowness of authorities. This paper examines the phenomenon of sarcasm as a tool of public criticism, particularly when responding to statements made by officials that were perceived as disappointing. Using a pragmatic approach and critical discourse analysis, this study finds that sarcasm does not emerge without reason; rather, it arises from a striking mismatch between officials’ statements and the harsh realities on the ground, compounded by responses that appeared half-hearted and lacking in empathy in communication. The findings show that sarcasm has become an effective means for the public to voice dissatisfaction amid the dominance of social media, while simultaneously signaling a crisis in disaster communication governance that urgently needs improvement.